GROWTH RESPONSE OF Caulerpa racemosa ON DIFFERENT CULTURE MEDIA (CONTAINERS VS. TARPAULINS) UNDER CONTROLLED CONDITIONS - Ma'rufa Nurul Latifah; Jane Lulinda Dangeubun; Irwan Ismail; Moses Tjoanda; Ongen Rumaryo Lekirupy (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2026)
Caulerpa racemosa is a commercially valuable macroalga, and cultivation conditions can influence its growth performance. Differences in environmental stability across cultivation media can lead to variations in stolon growth, ramification, and biomass accumulation, necessitating an evaluation of the optimal cultivation system under controlled conditions. The objective of this study was to compare the growth of primary stolons, ramules, and fresh biomass of C. racemosa cultivated in containers and tarpaulin tanks, and to determine the most effective medium for supporting vegetative growth in a controlled environment. This study employed a Completely Randomized Design (CRD) with two cultivation medium treatments (recycled water containers and tarpaulin tanks) over 30 days, with the containers maintained under similar environmental conditions, including controlled light intensity, salinity, and water circulation. Growth parameters (stolon length, ramification, and fresh biomass) were measured and compared across treatments. Stolon growth in the container medium reached an average length of 21.7–24.0 cm, whereas in the tarpaulin trough it ranged from 11.0 to 20.6 cm. Growth in the container medium was optimal due to more stable environmental conditions (smaller fluctuations in temperature and pH) and was statistically significantly higher than other treatments (p < 0.05). Containers can be recommended as an efficient cultivation medium for C. racemosa at the laboratory and pre-production scales, owing to their greater environmental stability and improved growth performance. Further research is recommended to evaluate nutrient optimization and scalability for coastal aquaculture applications.